Thailand Insurance Core Principles - International Monetary Fund; World Bank Group (World Bank, Washington, DC, 2019)
The Thai insurance sector is a relatively small but growing part of the country’s financial services industry. Insurance sector assets have grown from 10 percent of gross domestic product (GDP) in 2006 to over 22 percent of GDP in 2016, constituting 9 percent of total financial industry assets. Similarly, between 2008 and 2017, gross premiums written have grown at an average annual rate of approximately 16.9 percent, substantially above nominal GDP growth of 9.9 percent during the same period. As a result, the insurance penetration ratio (the ratio of premiums written to GDP) has gradually increased from 3.63 percent in 2008 to 5.39 percent in 2017. This paper provides an assessment of significant regulatory and supervisory practices in the insurance sector of Thailand. The assessment was conducted by Charles Michael Grist, Financial Sector Consultant, the World Bank Group, and A. Thomas Finnell, Financial Sector Consultant to the International Monetary Fund, from February 6 until February 22, 2019. The last review of the Thai insurance sector was conducted as part of an April 2008 Financial Sector Assessment Program Review (FSAP), but this review did not include a detailed assessment against the ICPs issued by the International Association of Insurance Supervisors (IAIS).